Optimalisasi Pembelajaran Agama Islam Integratif Inklusif untuk Meningkatkan Kualitas Pendidikan di Sekolah Dasar : Penelitian - Baehaqi, Faizal; M. Misbah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to optimize the teaching of Islamic Religious Education (PAI) in elementary schools through an integrative and inclusive approach, in order to enhance the quality of education that is relevant and comprehensive for all students. The method used is a case study with a qualitative approach, to explore the implementation of integrative teaching practices that combine Islamic values with general subjects, as well as an inclusive approach that involves students with special needs. The results of the study show that integrative learning can improve students' understanding of Islamic teachings in the context of daily life by linking religious values to other subjects. Meanwhile, the inclusive approach provides an opportunity for all students, including those with special needs, to actively engage in the learning process. The use of experiential learning methods, projects, and group discussions has been shown to increase student involvement and motivation. However, there are still challenges in its implementation, particularly related to teacher training and the availability of supporting facilities. This study recommends enhancing professional teacher training and developing adequate resources as strategic steps to support the success of integrative and inclusive Islamic Religious Education (PAI) teaching in elementary schools.